Bioinspired mechanically stable all-polysaccharide based scaffold for photosynthetic production - Virkkala Tuuli; Kosourov Sergey; Rissanen Ville; Siitonen Vilja; Arola Suvi; Allahverdiyeva Yagut; Tammelin Tekla (ROYAL SOC CHEMISTRY, 2025)
We demonstrate the construction of water-stable, biocompatible and self-standing hydrogels as scaffolds for the photosynthetic production of ethylene using a bioinspired all-polysaccharidic design combining TEMPO-oxidised cellulose nanofibers (TCNF) and a cereal plant hemicellulose called mixed-linkage glucan (MLG). We compared three different molecular weight MLGs from barley to increase the wet strength of TCNF hydrogels, and to reveal the mechanisms defining the favourable interactions between the scaffold components. The interactions between MLGs and TCNF were revealed via adsorption studies and interfacial rheology investigations using quartz crystal microbalance with dissipation monitoring (QCM-D). Our results show that both the MLG solution stability and adsorption behaviour did not exactly follow the well-known polymer adsorption and solubility theories especially in the presence of co-solute ions, in this case nitrates. We prepared hydrogel scaffolds for microalgal immobilisation, and high wet strength hydrogels were achieved with very low dosages of MLG (0.05 wt%) to the TCNF matrix. The all-polysaccharic biocatalytic architectures remained stable and produced ethylene for 120 h with yields comparable to the state-of-the-art scaffolds. Due to its natural origin and biodegradability, MLG offers a clear advantage in comparison to synthetic scaffold components, allowing the mechanical properties and water interactions to be tailored.